Influence of fibres on the resilient modulus and expansion of clayey subgrade soils - Madrid Argomedo, Manuel Ricardo (2024)
Expansive clayey soils at the subgrade level of roads and highways in different cities can affect the performance and durability of pavements. This increases the need for maintenance and conservation work, leading to higher operating costs. Traditionally, clayey soils are stabilised by adding lime or cement. However, the handling and use of these materials are restricted in some Latin American countries due to illegal drug production, and obtaining high-quality materials from distant sources can be impractical. The goal of this study is to determine the effectiveness of incorporating fibres in improving the performance of expansive clayey subgrade soils. To achieve this goal, resilient modulus tests and measurements of compacted soil expansion were performed. Two types of fibres were selected for this study: natural Ichu fibre, which is common in the Peruvian Andes, and polypropylene fibre. The soil used was a high-plasticity clay from the city of Pucallpa, to which varying percentages of fibres were incorporated (0.25%, 0.5% and 1%). The samples were prepared with a gyratory compactor to achieve their maximum dry density as obtained with the standard compaction effort. The results indicated that the incorporation of fibres improved the value of the resilient modulus while significantly reducing soil swelling.